Bioinspired Rhamnolipid Protects Wheat Against Zymoseptoria tritici Through Mainly Direct Antifungal Activity and Without Major Impact on Leaf Physiology - Platel, Rémi; Lucau-Danila, Anca; Baltenweck, Raymonde; Maia-Grondard, Alessandra; Chaveriat, Ludovic; Magnin-Robert, Maryline; Randoux, Béatrice; Trapet, Pauline; Halama, Patrice; Martin, Patrick; Hilbert, Jean-Louis; Höfte, Monica; et al. (Frontiers in Plant Science, 2022)
Rhamnolipids (RLs), glycolipids biosynthesized by Pseudomonas and Burkholderia genera, are known to display various activities against a wide range of pathogens. Most of the previous studies on RLs focused on their direct antimicrobial activity, while only a few reports described the mechanisms by which RLs induce resistance against phytopathogens and the related fitness cost on plant physiology. We combined here transcriptomic and metabolomic approaches to unravel the mechanisms underlying RL induced resistance in wheat against the hemibiotrophic fungus Zymoseptoria tritici, a major pathogen on this crop. The investigations were carried out by treating wheat plants with a bioinspired synthetic mono-RL with a 12-carbon fatty acid tail, dodecanoyl α/β-L-rhamnopyranoside (Rh-Est-C12), in both infectious and non-infectious conditions, to examine its potential wheat defense eliciting as well as priming bioactivities. Whereas Rh-Est-C12 conferred to wheat a significant protection against Z. tritici (41% disease severity reduction), only a slight effect of this RL on wheat leaf gene expression and metabolite accumulation was observed. A subset of 24 differentially expressed genes (DEGs) and 11 differentially accumulated metabolites (DAMs) were scored in elicitation modalities at two, five, and fifteen days post-treatment (dpt), and 25 DEGs and 17 DAMs were recorded in priming modalities at five and fifteen dpt. Most of the changes were down-regulations and only a few DEGs and DAMs associated with resistance to pathogens were identified. Nevertheless, a transient early regulation in gene expression was highlighted at two dpt (e.g. genes involved in signaling, transcription, translation, cell-wall structure, and function), suggesting a perception of the RL by the plant upon treatment. Further in vitro and in planta bioassays showed that Rh-Est-C12 displays a significant direct antimicrobial activity towards Z. tritici. Taken together, our results suggest that Rh-Est-C12 confers protection to wheat against Z. tritici through direct antifungal activity and to a lesser extent via the induction of plant defenses, without causing major alterations of the plant metabolism. This study provides new insights into the modes of action of RLs on the wheat-Z. tritici pathosystem and highlights the potential interest of Rh-Est-C12, a low-fitness cost molecule, to control this pathogen.